Yield and Quality of Head Lettuce (Lactuca sativa var. capitata L.) subject to Amount of Multi- Purpose Organic Fertilizer “Dominanta” Applied and Density of Plants Disposition - А. В. Андрющенко; Н. В. Лещук; М. А. Броновицька; І. В. Дидів; О. Й. Дидів (Plant Varieties Studying and Protection)
Optimal amounts of new organic universal fertilizer “Dominanta” applied for treatment of Head Lettuce of Smuglianka variety have been established by complex of field and laboratory experiments. Techniques and rates and terms of the organic fertilizer application that provide high feasible biological yield and quality of merchantable heads of Cutting Lettuce have been rationalized.